The study of the effect on soil fertility and Arabica coffee seed quality under monoculture and integrated farming in Ban Pang Khon, Chiang Rai Province - Panyamaneesorn, Wathana; Tunma, Somruthai (วารสารแก่นเกษตร, 2024)
This research aimed to study the soil properties and the quality of Arabica coffee seeds of the Catimor variety under the agroforestry system with temperate fruit trees in a naturally regenerated mixed and monoculture area at Ban Pang Khon. It was focused on promoting high-quality coffee cultivation in highland areas and maintaining sustainable environmental systems. Randomly arranged sample plots of size 50x20 square meters were established. Soil samples were collected from the same level of depth (0-15 cm) in both monoculture and agroforestry areas. Coffee seeds were randomly collected from each plot, totaling 600 seeds per plot. The results showed that the soil of the single-crop coffee garden is loamy sand, while the mixed-crop soil is a loam soil mixed with sand. The soils in the monoculture and agroforestry areas were slightly acidic to moderately acidic (pH 5.42-5.35). The electrical conductivity (EC) of the soil was between 25.79-27.61 μS/cm, indicating a non-saline soil. The organic matter content (%OM) in the soil ranged from 6.55% to 6.08%. The organic carbon content (%OC) was high, with main nutrient levels: N = 0.38-0.50%, P = 10.37-14.43 mg/kg, and K = 215.04-508.95 mg/kg. The cation exchange capacity (CEC) ranged from 18.53 to 20.22 meq/100g. Soils from the agroforestry area exhibited higher CEC and moisture content compared to monoculture soils, indicating the ability to retain nutrients in the soil and higher soil fertility. Fresh coffee beans from the agroforestry area contained 1,082.56 mg/kg of caffeine, 188.09 mg Gallic acid/g dry weight (DW) of total phenolic compounds, and higher antioxidant activity than coffee beans from the monoculture area, which contained 783.43 mg/kg of caffeine, 135.54 mg Gallic acid/g DW of total phenolic compounds, and 8.60 mg Vitamin C/g DW. Therefore, the agroforestry system for Arabica coffee cultivation has positive effects on soil properties and soil